Cyberhealth serving to support individual intake of medication (Swiss Medical Weekly, 2013)
The Internet and new communication technologies are deeply affecting healthcare systems and the provision of care. The purpose of this article is to evaluate the possibility that cyberhealth, via the development of widespread easy access to wireless personal computers, tablets and smartphones, can effectively influence intake of medication and long-term medication adherence, which is a complex, difficult and dynamic behaviour to adopt and to sustain over time. Because of its novelty, the impact of cyberhealth on drug intake has not yet been well explored. Initial results have provided some evidence, but more research is needed to determine the impact of cyberhealth resources on long-term adherence and health outcomes, its user-friendliness and its adequacy in meeting e-patient needs. The purpose of such Internet-based interventions, which provide different levels of customisation, is not to take over the roles of healthcare providers; on the contrary, cyberhealth platforms should reinforce the alliance between healthcare providers and patients by filling time-gaps between visits and allowing patients to upload and/or share feedback material to be used during the visits. This shift, however, is not easily endorsed by healthcare providers, who must master new eHealth skills, but healthcare systems have a unique opportunity to invest in the Internet and to use this powerful tool to design the future of integrated care. Before this can occur, however, important issues must be addressed and resolved, for example ethical considerations, the scientific quality of programmes, reimbursement of activity, data security and the ownership of uploaded data.